CAPITAL BUDGETING PRACTICES IN VIETNAM: A SURVEY OF CONSTRUCTION INVESTMENT FIRMS - Tran Tung, Linh (2009)
The main intention of this research is to investigate how the Vietnamese firms evaluate the construction investment projects. The research is conducted by qualitative method by sending questionnaires to Vietnamese firms who specialize in construction investment field. Several questions are raised in the questionnaires which are categorized into four parts: evaluation techniques, risk analysis, discount rate and free cash flow forecasting. The distinction between Vietnamese capital budgeting would be made by comparing to the previous researches in the UK, US and Asian countries. This research, in addition, also explores how the Vietnamese firms produce the cash flow forecast and deal with the uncertainties of economy.